The Economic Value of Job Crafting Interventions in Healthcare: An Utility Analysis Based on Romanian Income Data - Adriana COTEL; Bogdan OPREA; Florinda GOLU; Claudiu Gabriel IONESCU; Monica LICU (Modern Medicine)
Objectives: The aim of the study was to estimate the economic value of job crafting interventions for the Romanian medical field. Materials and Methods: The utility analysis was used, representing the evaluation of the economic impact of human resource management solutions based on mathematical formulas. Meta analytical data show that job crafting interventions have a positive impact on the performance of healthcare workers. We estimated the financial value of these psychological interventions in three ways: monetary increase in productivity, percentage increase in productivity, and reduction in labor costs. Outcomes: The results indicate substantial benefits for the healthcare field as a result of job crafting interventions, as measured by monetary increases in productivity. The percentage increase in productivity was estimated at 14% for a period of three months. The reduction in labor costs was estimated at 12% over a three-month period. Conclusions: Job crafting interventions could have a significant economic value for the Romanian medical sector.